Building a Software System Using a Spiral Model to Evaluate the Overall Risk of Projects Using Fuzzy Number Theory - Jamal Sayed Majeed; Ro’a Amer Hussain (Al-Rafidain Journal of Computer Sciences and Mathematics)
This research aims presented a practical application for the process of assessing the overall risk of the projects following the risk management in software engineering steps, the life cycle is the most famous in this area is a (Spiral Model), this model represented by the core of the process to building a system based on customers information taken from them in the form of hearings conversations. This research depended on EA tool (Enterprise Architect) that building by a company (Sparex Systems) for represent the processes of stages to analysis because it is the basis currently used in the world and the most prevalent and most recently the base idea for this work is found the rate of aggregative risk in project by used fuzzy model for fuzzy number by follow Lee's algorithm. This system has been applied a practical in bank / public administration / northern region of the data / analysis and risk assessment of bank credit / short-term and long-term.